One class of solutions of Volterra equations with regular singularity - Krein, S. G.; Sapronov, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
The Volterra integral equation of the second order with a regular singularity is considered. Under the conditions that a kernel K(x,t) is a real matrix function of order n×n with continuous partial derivatives up to order N+1 inclusively and K(0,0) has complex eigenvalues ν±i μ (ν>0), it is shown that if ν>2|‖K|‖ C -N-1, then a given equation has two linearly independent solutions.